Salmonella spp in wild birds living around a well-managed guinea pig farm in the district of Manchay, Lima - Espinoza Ramírez, Kathya (2019)
The objective of the present study was to determine the presence of Salmonella spp in wild birds that live in the surroundings of a well-managed guinea pig farm. Free-living wild birds were captured (n=185) and eight species were identified: Passer domesticus (63.8%), Volatinia jacarina (16.8%), Troglodytes aedon (2.2%), Pyrocephalus rubinus (1.1%), Molothrus bonariensis (0.5%), Crotophaga sulcirostris (1.1%), Columbina cruziana (12.9%) and Forpus coelestis (1.6%). Samples were taken through cloacal swab. Salmonella spp was isolated in 4.32% (8/185) of the wild birds, but only in Passer domesticus, Volatinia jacarina and Forpus coelestis. Likewise, two enrichment methods were used, obtaining 2.2% (4/185) of samples positive for Salmonella spp with standard enrichment and 3.8% (7/185) with delayed enrichment.